High-strength outdoor compartment water-based paint and preparation method thereof

By compounding dendritic silica and carboxyl-modified polystyrene microspheres, a water-based UV-curing coating with high cross-linking density is constructed, which solves the problems of insufficient flexibility, wear resistance and aging resistance of outdoor water-based coatings, achieves high impact resistance and long-term weather resistance of the coating, and improves the performance of outdoor compartments.

CN120665506AActive Publication Date: 2025-09-19DAYU SONGYING CHEM CO LTD
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
CN202511156824.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-09-19
Estimated Expiration
2045-08-19

AI Technical Summary

Technical Problem

Existing outdoor water-based coatings have problems such as poor flexibility, insufficient wear resistance, and weak aging resistance in long-term use, which makes it difficult to meet the comprehensive requirements of outdoor compartments for high impact resistance and long-term weather resistance.

Method used

By compounding dendritic silica and carboxyl-modified polystyrene microspheres and using a high-crosslinking-density water-based UV curing system, a dense coating structure is constructed to enhance the mechanical strength and impact resistance, improve the flexibility and wear resistance of the coating, and through the synergistic effect of dendritic silica and carboxyl-modified polystyrene microspheres, the thermal stability and environmental adaptability of the coating are improved.

Benefits of technology

It significantly improves the wear resistance and weather resistance of the coating, extends the service life of the coating, and ensures excellent appearance and performance stability in outdoor environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120665506A_ABST
    Figure CN120665506A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water-based paint, in particular to high-strength outdoor compartment water-based paint and a preparation method thereof. The high-strength outdoor compartment water-based paint is prepared from the following raw materials in parts by mass: 30 to 40 parts of water-based aliphatic polyurethane acrylate resin, 5 to 15 parts of water-based ultraviolet curing polyurethane dispersion, 1 to 5 parts of carboxyl modified polystyrene microspheres, 6 to 15 parts of dendritic silicon dioxide, 1 to 5 parts of photoinitiator and 1 to 5 parts of polyethylene glycol diacrylate monomer. The adhesive is prepared from the following components in parts by weight: 1-5 parts of a polydipentaerythritol hexaacrylate monomer, 1-5 parts of dipropylene glycol monomethyl ether, 1-5 parts of propylene glycol and 5-10 parts of an auxiliary material. The water-based UV curing system is adopted, the curing speed is high, the crosslinking degree is high, the weather resistance and yellowing resistance of the coating can be effectively improved, the coating keeps excellent appearance and performance stability in long-term outdoor use, and the preparation method is simple and suitable for large-scale application and popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water-based paints, and in particular to a high-strength outdoor vehicle body water-based paint and a preparation method thereof. Background Art

[0002] Water-based UV coatings have become a research hotspot in the coatings industry, as they combine the low VOC emissions of water-based coatings with the rapid curing properties of UV-curable coatings. However, existing outdoor water-based coatings on the market generally suffer from poor flexibility and impact resistance, insufficient abrasion resistance, and weak aging resistance. These problems lead to cracking, yellowing, blistering, gloss loss, and paint peeling after long-term use, making them difficult to meet the long-term weather resistance and mechanical performance requirements of outdoor vehicles.

[0003] Outdoor van coatings are subject to long-term exposure to sunlight, rain, acid rain, dust, alternating hot and cold weather, and microbial attack, requiring excellent aging resistance. While traditional water-based coatings are environmentally friendly, they suffer from slow curing speeds and low crosslinking densities, resulting in insufficient aging resistance. Traditional UV coatings, while fast-curing and high-hardness, suffer from significant shrinkage and poor flexibility, making them difficult to adapt to thermal expansion and contraction in outdoor environments.

[0004] By incorporating UV curing technology, water-based UV coatings significantly improve the crosslinking density and mechanical properties of the coating while maintaining low VOC emissions, effectively addressing the slow curing and insufficient weather resistance of traditional water-based coatings. However, existing water-based UV coatings struggle to simultaneously meet the combined requirements of high impact resistance and long-term weather resistance for outdoor vehicles.

[0005] Therefore, developing a water-based outdoor body coating with high flexibility, excellent wear resistance and aging resistance is of great significance for improving the long-term performance of the coating and reducing maintenance costs. Summary of the Invention

[0006] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high-strength outdoor car body water-based paint and a preparation method thereof.

[0007] A high-strength outdoor car body water-based paint, the raw materials of which include, by mass: 30-40 parts of water-based aliphatic polyurethane acrylate resin, 5-15 parts of water-based UV-curable polyurethane dispersion, 1-5 parts of carboxyl-modified polystyrene microspheres, 6-15 parts of dendritic silica, 1-5 parts of photoinitiator, 1-5 parts of polyethylene glycol diacrylate monomer, 1-5 parts of polydipentaerythritol hexaacrylate monomer, 1-5 parts of dipropylene glycol methyl ether, 1-5 parts of propylene glycol, and 5-10 parts of auxiliary materials.

[0008] Preferably, the photoinitiator comprises: 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone, and the mass ratio of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide to 1-hydroxy-cyclohexyl-phenyl ketone is 0.5-1.5:1.

[0009] Preferably, the auxiliary materials include: a wetting agent, a defoaming agent, a leveling agent, a pH regulator, and a thickener.

[0010] More preferably, the mass ratio of the wetting agent, the defoaming agent, the leveling agent, the pH regulator and the thickener is 1-2:1-2:1-2:1-2:1-2.

[0011] Preferably, the dendritic silica is prepared by the following steps: adding the dendritic polymer template to an ethanol aqueous solution and stirring for 10-30 minutes, adding an ammonia aqueous solution dropwise thereto while stirring, and continuing to stir for 5-15 minutes, adding ethyl orthosilicate dropwise thereto while stirring, stirring for 5-10 hours, standing for 10-15 hours, adding a silane coupling agent and stirring for 1-2 hours, centrifuging, washing, and vacuum drying.

[0012] More preferably, the mass fraction of the ammonia solution is 15-20%, and the mass ratio of the dendrimer template, the ammonia solution, the tetraethyl orthosilicate, and the silane coupling agent is 1-3:5-10:5-12:0.1-1.

[0013] More preferably, the dendrimer template is amino-terminated polyamidoamine or hyperbranched polylysine.

[0014] Preferably, the carboxyl-modified polystyrene microspheres are prepared by the following steps: adding the polystyrene microspheres to an ethanol aqueous solution and stirring evenly, adding azobisisobutyronitrile, α-methylacrylic acid, and styrene under nitrogen protection, stirring at 60-80° C. for 5-15 hours, filtering, washing, drying, and crushing.

[0015] More preferably, the mass ratio of polystyrene microspheres, azobisisobutyronitrile, α-methacrylic acid, and styrene is 1-5: 0.01-0.1: 0.1-0.2: 0.1-0.5.

[0016] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix water-based aliphatic polyurethane acrylate resin and water-based UV-curable polyurethane dispersion, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 10-30 minutes to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials into water and stir for 10-30 minutes. Add premix and continue stirring for 10-20 minutes, and filter.

[0017] Beneficial effects:

[0018] The present invention uses a dendritic polymer (amino-terminated polyamide-amine or hyperbranched polylysine) as a template to guide the hydrolysis and deposition of tetraethyl orthosilicate to form silica particles with a dendritic structure. Surface grafting modification is performed using a silane coupling agent to effectively inhibit particle agglomeration and improve their dispersion uniformity in the resin system.

[0019] Dendritic silica, with its unique three-dimensional branching structure, forms a multi-level dispersed network within the coating, enhancing the coating's mechanical strength and impact resistance. Dendritic silica's large surface area and highly reactive sites enable chemical bonding with reactive groups in the resin (such as isocyanate and carboxyl groups), effectively filling micropores and defects within the coating and improving its density and surface hardness.

[0020] The carboxyl-modified polystyrene microspheres introduced into the system exhibit excellent elasticity and deformation recovery, effectively absorbing external impact energy and preventing the coating from cracking or shedding when subjected to external forces, thereby significantly improving the coating's flexibility and impact resistance. Furthermore, the carboxyl-modified polystyrene microspheres form a uniformly distributed elastic support structure within the coating, effectively dispersing external friction and reducing wear on the coating surface. The synergistic effect significantly enhances the coating's wear resistance and extends its service life over long-term use.

[0021] The present invention constructs a stable and dense coating structure through the synergistic effect of a high-crosslinking density resin system and functional fillers, effectively blocking the erosion of the coating by the external environment (such as ultraviolet rays, acid rain, oxygen, moisture, etc.), and uses dendritic silica and carboxyl-modified polystyrene microspheres to compound the coating, so that the coating has good thermal stability and environmental adaptability, which can effectively alleviate the deformation and aging of the coating in environments such as alternating hot and cold and high humidity.

[0022] The present invention adopts a water-based UV curing system with a fast curing speed and high cross-linking degree, which can effectively improve the weather resistance and anti-yellowing ability of the coating, so that the coating maintains excellent appearance and performance stability during long-term outdoor use. The preparation method is simple and suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The figure is a comparison chart of the impact resistance and abrasion resistance of the coatings made by using the high-strength outdoor car body water-based paint obtained in Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0024] The present invention will be further explained below with reference to specific embodiments.

[0025] The water-based aliphatic polyurethane acrylate resin used below is from allnex resins, brand UCECOAT ® 7230. The aqueous UV-curable polyurethane dispersion used below is from Covestro, brand Bayhydrol® UV 2282. The polyethylene glycol diacrylate monomer used below is purchased from Guangdong Moutai New Materials Co., Ltd., specifically PEG200DA (a low molecular weight, difunctional monomer in the polyethylene glycol diacrylate series). The polydipentaerythritol hexaacrylate monomer used below is dipentaerythritol hexaacrylate, purchased from Guangzhou Moushi Biotechnology Co., Ltd.

[0026] The following auxiliary materials are composed of a wetting agent, a defoaming agent, a leveling agent, a pH regulator, and a thickener in a mass ratio of 1:1:1:1:1; the wetting agent, defoaming agent, leveling agent, pH regulator, and thickener are all from BYK in Germany, such as the wetting agent is BYK-190 and the defoaming agent is BYK-028.

[0027] Example 1

[0028] A high-strength outdoor box water-based paint, whose raw materials include: 300g of water-based aliphatic polyurethane acrylate resin, 50g of water-based UV-curable polyurethane dispersion, 10g of carboxyl-modified polystyrene microspheres, 60g of dendritic silica, 10g of photoinitiator, 10g of polyethylene glycol diacrylate monomer, 10g of polydipentaerythritol hexaacrylate monomer, 10g of dipropylene glycol methyl ether, 10g of propylene glycol, and 50g of auxiliary materials.

[0029] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 0.5:1.

[0030] Dendritic silica was prepared by the following steps: 10 g of hyperbranched polylysine was added to 500 g of a 50% ethanol aqueous solution, stirred at 1000 r / min for 10 min, 50 g of a 15% ammonia aqueous solution was added dropwise while stirring, and stirring was continued for 5 min. 50 g of ethyl orthosilicate was added dropwise while stirring, and stirred for 5 h. The mixture was allowed to stand for 10 h, 1 g of a silane coupling agent KH-550 was added, and the mixture was stirred at 100 r / min for 1 h. The mixture was centrifuged, washed alternately with ethanol and deionized water, and dried in vacuo.

[0031] Carboxyl-modified polystyrene microspheres were prepared by the following steps: 10 g of polystyrene microspheres with a particle size of 200-500 nm were added to 200 g of 60% ethanol aqueous solution and stirred evenly. Under nitrogen protection, 0.1 g of azobisisobutyronitrile, 1 g of α-methylacrylic acid, and 1 g of styrene were added thereto. The mixture was stirred at 60°C for 5 h, filtered, washed, dried, and crushed.

[0032] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix the water-based aliphatic polyurethane acrylate resin and the water-based UV-curable polyurethane dispersion evenly, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 10 minutes at a stirring speed of 100 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 100 g of water, stir at a speed of 1000 r / min for 10 min, add premix and continue stirring for 10 min, and filter.

[0033] Example 2

[0034] A high-strength outdoor box water-based paint, whose raw materials include: 400g of water-based aliphatic polyurethane acrylate resin, 150g of water-based UV-curable polyurethane dispersion, 50g of carboxyl-modified polystyrene microspheres, 150g of dendritic silica, 50g of photoinitiator, 50g of polyethylene glycol diacrylate monomer, 50g of polydipentaerythritol hexaacrylate monomer, 50g of dipropylene glycol methyl ether, 50g of propylene glycol, and 100g of auxiliary materials.

[0035] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 1.5:1.

[0036] Dendritic silica was prepared by the following steps: 30 g of amino-terminated polyamide-amine (G2.0) was added to 600 g of 60% ethanol aqueous solution, stirred at 1500 r / min for 30 min, 100 g of 20% ammonia aqueous solution was added dropwise while stirring, and stirring was continued for 15 min. 120 g of ethyl orthosilicate was added dropwise while stirring, stirred for 10 h, allowed to stand for 15 h, 10 g of silane coupling agent KH-550 was added, stirred at 300 r / min for 2 h, centrifuged, washed alternately with ethanol and deionized water, and dried under vacuum.

[0037] Carboxyl-modified polystyrene microspheres were prepared by the following steps: 50 g of polystyrene microspheres with a particle size of 200-500 nm were added to 400 g of 70% ethanol aqueous solution and stirred evenly. Under nitrogen protection, 1 g of azobisisobutyronitrile, 2 g of α-methylacrylic acid, and 5 g of styrene were added thereto. The mixture was stirred at 80°C for 15 h, filtered, washed, dried, and crushed.

[0038] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix the water-based aliphatic polyurethane acrylate resin and the water-based UV-curable polyurethane dispersion, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 30 minutes at a stirring speed of 400 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 300 g of water, stir at a speed of 1500 r / min for 30 min, add premix and continue stirring for 20 min, and filter.

[0039] Example 3

[0040] A high-strength outdoor car body water-based paint, whose raw materials include: 330g of water-based aliphatic polyurethane acrylate resin, 120g of water-based UV-curable polyurethane dispersion, 20g of carboxyl-modified polystyrene microspheres, 120g of dendritic silica, 20g of photoinitiator, 40g of polyethylene glycol diacrylate monomer, 20g of polydipentaerythritol hexaacrylate monomer, 40g of dipropylene glycol methyl ether, 20g of propylene glycol, and 80g of auxiliary materials.

[0041] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 0.8:1.

[0042] Dendritic silica was prepared by the following steps: 25 g of amino-terminated polyamide-amine (G3.0) was added to 520 g of 57% ethanol aqueous solution, stirred at 1100 r / min for 25 min, 70 g of 18% ammonia aqueous solution was added dropwise while stirring, and stirring was continued for 8 min. 100 g of ethyl orthosilicate was added dropwise while stirring, stirred for 7 h, allowed to stand for 13 h, 3 g of silane coupling agent KH-550 was added, stirred at 250 r / min for 80 min, centrifuged, washed alternately with ethanol and deionized water, and dried in vacuo.

[0043] Carboxyl-modified polystyrene microspheres were prepared by the following steps: 40 g of polystyrene microspheres with a particle size of 200-500 nm were added to 250 g of 68% ethanol aqueous solution and stirred evenly. Under nitrogen protection, 0.3 g of azobisisobutyronitrile, 1.8 g of α-methylacrylic acid, and 2 g of styrene were added thereto. The mixture was stirred at 75°C for 8 h, filtered, washed, dried, and crushed.

[0044] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix the water-based aliphatic polyurethane acrylate resin and the water-based UV-curable polyurethane dispersion, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 25 minutes at a stirring speed of 200 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 250 g of water, stir at a speed of 1100 r / min for 25 min, add premix and continue stirring for 12 min, and filter.

[0045] Example 4

[0046] A high-strength outdoor car body water-based paint, whose raw materials include: 370g of water-based aliphatic polyurethane acrylate resin, 80g of water-based UV-curable polyurethane dispersion, 40g of carboxyl-modified polystyrene microspheres, 80g of dendritic silica, 40g of photoinitiator, 20g of polyethylene glycol diacrylate monomer, 40g of polydipentaerythritol hexaacrylate monomer, 20g of dipropylene glycol methyl ether, 40g of propylene glycol, and 70g of auxiliary materials.

[0047] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 1.2:1.

[0048] Dendritic silica was prepared by the following steps: 15 g of amino-terminated polyamide-amine (G2.5) was added to 580 g of 53% ethanol aqueous solution, stirred at 1300 r / min for 15 min, 90 g of 16% ammonia aqueous solution was added dropwise while stirring, and stirring was continued for 12 min. 60 g of ethyl orthosilicate was added dropwise while stirring, stirred for 9 h, allowed to stand for 11 h, 7 g of silane coupling agent KH-550 was added, stirred at 150 r / min for 100 min, centrifuged, washed alternately with ethanol and deionized water, and dried in vacuo.

[0049] Carboxyl-modified polystyrene microspheres were prepared by the following steps: 20 g of polystyrene microspheres with a particle size of 200-500 nm were added to 350 g of 62% ethanol aqueous solution and stirred evenly. Under nitrogen protection, 0.7 g of azobisisobutyronitrile, 1.2 g of α-methylacrylic acid, and 4 g of styrene were added thereto. The mixture was stirred at 65°C for 12 h, filtered, washed, dried, and crushed.

[0050] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix the water-based aliphatic polyurethane acrylate resin and the water-based UV-curable polyurethane dispersion evenly, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 15 minutes at a stirring speed of 300 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 150 g of water, stir at a speed of 1300 r / min for 15 min, add premix and continue stirring for 18 min, and filter.

[0051] Example 5

[0052] A high-strength outdoor box water-based paint, whose raw materials include: 350g of water-based aliphatic polyurethane acrylate resin, 100g of water-based UV-curable polyurethane dispersion, 30g of carboxyl-modified polystyrene microspheres, 100g of dendritic silica, 30g of photoinitiator, 30g of polyethylene glycol diacrylate monomer, 30g of polydipentaerythritol hexaacrylate monomer, 30g of dipropylene glycol methyl ether, 30g of propylene glycol, and 75g of auxiliary materials.

[0053] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 1:1.

[0054] Dendritic silica was prepared by the following steps: 20 g of amino-terminated polyamide-amine (G2.5) was added to 550 g of 55% ethanol aqueous solution, stirred at 1200 r / min for 20 min, 80 g of 17% ammonia aqueous solution was added dropwise while stirring, and stirring was continued for 10 min. 80 g of ethyl orthosilicate was added dropwise while stirring, stirred for 8 h, allowed to stand for 12 h, 5 g of silane coupling agent KH-550 was added, stirred at 200 r / min for 90 min, centrifuged, washed alternately with ethanol and deionized water, and dried in vacuo.

[0055] Carboxyl-modified polystyrene microspheres were prepared by the following steps: 30 g of polystyrene microspheres with a particle size of 200-500 nm were added to 300 g of 65% ethanol aqueous solution and stirred evenly. Under nitrogen protection, 0.5 g of azobisisobutyronitrile, 1.5 g of α-methylacrylic acid, and 3 g of styrene were added thereto. The mixture was stirred at 70°C for 10 h, filtered, washed, dried, and crushed.

[0056] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix water-based aliphatic polyurethane acrylate resin and water-based UV-curable polyurethane dispersion evenly, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 20 minutes at a stirring speed of 250 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 200 g of water, stir at a speed of 1200 r / min for 20 min, add premix and continue stirring for 15 min, and filter.

[0057] Comparative Example 1 A high-strength outdoor box water-based paint, whose raw materials include: 350g of water-based aliphatic polyurethane acrylate resin, 100g of water-based UV-curable polyurethane dispersion, 30g of carboxyl-modified polystyrene microspheres, 100g of dendritic silica, 30g of photoinitiator, 30g of polyethylene glycol diacrylate monomer, 30g of polydipentaerythritol hexaacrylate monomer, 30g of dipropylene glycol methyl ether, 30g of propylene glycol, and 75g of auxiliary materials.

[0058] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 1:1.

[0059] Dendritic silica was prepared by the following steps: 80 g of 17% ammonia solution was added dropwise to 550 g of 55% ethanol aqueous solution, and stirring was continued for 10 min. 80 g of ethyl orthosilicate was added dropwise thereto under stirring, and the mixture was stirred for 8 h. The mixture was allowed to stand for 12 h, and 5 g of silane coupling agent KH-550 was added. The mixture was stirred at 200 r / min for 90 min, centrifuged, and washed alternately with ethanol and deionized water. The mixture was vacuum dried, and 20 g of amino-terminated polyamide-amine (G2.5) was added and mixed evenly.

[0060] Carboxyl-modified polystyrene microspheres were prepared by the following steps: 30 g of polystyrene microspheres with a particle size of 200-500 nm were added to 300 g of 65% ethanol aqueous solution and stirred evenly. Under nitrogen protection, 0.5 g of azobisisobutyronitrile, 1.5 g of α-methylacrylic acid, and 3 g of styrene were added thereto. The mixture was stirred at 70°C for 10 h, filtered, washed, dried, and crushed.

[0061] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix water-based aliphatic polyurethane acrylate resin and water-based UV-curable polyurethane dispersion evenly, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 20 minutes at a stirring speed of 250 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 200 g of water, stir at a speed of 1200 r / min for 20 min, add premix and continue stirring for 15 min, and filter.

[0062] Comparative Example 2 A high-strength outdoor box water-based paint, whose raw materials include: 350g of water-based aliphatic polyurethane acrylate resin, 100g of water-based UV-curable polyurethane dispersion, 30g of polystyrene microspheres, 100g of dendritic silica, 30g of photoinitiator, 30g of polyethylene glycol diacrylate monomer, 30g of polydipentaerythritol hexaacrylate monomer, 30g of dipropylene glycol methyl ether, 30g of propylene glycol, and 75g of auxiliary materials.

[0063] The photoinitiator is composed of 2,4,6 (trimethylbenzoyl) diphenylphosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone in a mass ratio of 1:1.

[0064] Dendritic silica was prepared by the following steps: 20 g of amino-terminated polyamide-amine (G2.5) was added to 550 g of 55% ethanol aqueous solution, stirred at 1200 r / min for 20 min, 80 g of 17% ammonia aqueous solution was added dropwise while stirring, and stirring was continued for 10 min. 80 g of ethyl orthosilicate was added dropwise while stirring, stirred for 8 h, allowed to stand for 12 h, 5 g of silane coupling agent KH-550 was added, stirred at 200 r / min for 90 min, centrifuged, washed alternately with ethanol and deionized water, and dried in vacuo.

[0065] The preparation method of the above-mentioned high-strength outdoor car body water-based paint comprises the following steps: S1. Mix the water-based aliphatic polyurethane acrylate resin and the water-based UV-curable polyurethane dispersion evenly, add dendritic silica and polystyrene microspheres, and continue stirring for 20 minutes at a stirring speed of 250 r / min to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials to 200 g of water, stir at a speed of 1200 r / min for 20 min, add premix and continue stirring for 15 min, and filter.

[0066] The high-strength outdoor car body water-based paint obtained in Example 5 and Comparative Examples 1-2 was applied to the surface of tinplate sheets, dried at 50°C for 30 minutes, and then cured under a high-pressure ultraviolet mercury lamp (spectral energy distribution centered at 365 nm, transmission rate of 15 m / min). The coating thickness for each group was 50 ± 5 μm.

[0067] The hardness of each of the above coating samples was measured with reference to GB / T 6739-2022, "Paints and varnishes - Determination of film hardness by pencil method." The adhesion of each of the above coating samples was evaluated with reference to GB / T 9286-2021, "Paints and varnishes - Cross-cut test." The flexibility of each of the above coating samples was also measured with reference to GB / T 1731-2020, "Determination of the flexibility of paint and putty films." The results are shown in Table 1.

[0068] Table 1 Hardness, adhesion and flexibility results of the coatings obtained in Example 5 and Comparative Examples 1-2.

[0069] Example 5 Comparative Example 1 Comparative Example 2 Pencil hardness H B HB Cross-cut test Level 0 Level 1 Level 1 flexibility 1mm 2mm 4mm It can be seen from Table 1 that the hardness, adhesion and flexibility of the coating prepared by Example 5 are all the best, which are better than those of Comparative Examples 1-2.

[0070] The impact resistance of each of the above coating samples was tested with reference to GB / T 1732-2020, "Determination of impact resistance of paint films." (Because 50 kg·cm was insufficient for testing, additional weights were used for further testing.) The abrasion resistance (1000 g x 500 r) of each of the above coating samples was also tested with reference to GB / T 1768-2006, "Paints and varnishes - Determination of abrasion resistance - Rotating rubber grinding wheel method."

[0071] The results are as follows Figure 1 As shown, the coating prepared by Example 5 has the highest impact resistance and the lowest wear resistance, which is better than that of Comparative Examples 1-2 (P < 0.05).

[0072] Referring to GB / T 14522-2008, "Test Methods for Artificial Weathering of Plastics, Coatings, and Rubber Materials for Mechanical Industrial Products—Fluorescent UV Lamp," each group of coating samples was exposed to UV light for 52 weeks. Furthermore, referring to GB / T 33568-2017, "Grades and Evaluation Methods for Surface Aging of Outdoor Wood Finishes," the blistering and cracking levels of each group of coating samples after UV exposure were measured. The results are shown in Table 2.

[0073] Table 2 Aging resistance results of the coatings obtained in Example 5 and Comparative Examples 1-2.

[0074] Example 5 Comparative Example 1 Comparative Example 2 Number of bubbles Level 0 Level 2 Level 2 Bubble size S0 level S2 level S2 level Number of cracks Level 0 Level 1 Level 2 Crack size S0 level S2 level S2 level

[0075] It can be seen from Table 2 that the coating prepared by Example 5 has the best aging resistance, which is better than that of Comparative Examples 1-2.

[0076] The coating samples were subjected to thermal cycling in accordance with CNCIA-HG / T 0004-2012, "Test Methods for Thermal Cycling of Paint and Varnish Films." The blistering and cracking levels of the coating samples after thermal cycling were then measured in accordance with GB / T 33568-2017, "Grades and Evaluation Methods for Aging of Surface Finishes of Outdoor Wood." The results are shown in Table 3.

[0077] Table 3 Hot and cold cycle results of the coatings obtained in Example 5 and Comparative Examples 1-2.

[0078] Example 5 Comparative Example 1 Comparative Example 2 Number of bubbles Level 0 Level 1 Level 2 Bubble size S0 level S1 level S2 level Number of cracks Level 0 Level 1 Level 2 Crack size S0 level S2 level S2 level

[0079] It can be seen from Table 3 that the coating prepared by Example 5 has the best cold and hot cycle performance, which is better than that of Comparative Examples 1-2.

[0080] The reason for these results is that the present invention uses a dendritic polymer (amino-terminated polyamidoamine or hyperbranched polylysine) as a template to guide the hydrolysis and deposition of tetraethyl orthosilicate to form dendritic silica particles. Surface grafting with a silane coupling agent effectively inhibits particle aggregation and improves dispersion uniformity within the resin system. The dendritic silica, with its unique three-dimensional branched structure, forms a multi-level dispersed network within the coating, enhancing the coating's mechanical strength and impact resistance. The large surface area and high activity sites of the dendritic silica enable chemical bonding with active groups (such as isocyanate and carboxyl groups) in the resin, effectively filling micropores and defects within the coating and improving its density and surface hardness. The carboxyl-modified polystyrene microspheres introduced into the system exhibit excellent elasticity and deformation recovery, effectively absorbing external impact energy and preventing cracking or shedding of the coating under external forces, thereby significantly improving the coating's flexibility and impact resistance. At the same time, carboxyl-modified polystyrene microspheres form a uniformly distributed elastic support structure within the coating, effectively dispersing external friction and reducing wear on the coating surface. The combination of dendritic silica and carboxyl-modified polystyrene microspheres imparts excellent thermal stability and environmental adaptability to the coating, effectively mitigating deformation and aging in environments such as alternating hot and cold temperatures and high humidity. This significantly enhances the coating's wear resistance and extends its lifespan over long-term use.

[0081] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.

Claims

1. A high-strength outdoor car body water-based paint, characterized in that: The raw materials include, by mass, 30-40 parts of waterborne aliphatic polyurethane acrylate resin, 5-15 parts of waterborne ultraviolet light-curing polyurethane dispersion, 1-5 parts of carboxyl-modified polystyrene microspheres, 6-15 parts of dendritic silica, 1-5 parts of photoinitiator, 1-5 parts of polyethylene glycol diacrylate monomer, 1-5 parts of polydipentaerythritol hexaacrylate monomer, 1-5 parts of dipropylene glycol methyl ether, 1-5 parts of propylene glycol, and 5-10 parts of auxiliary materials.

2. The high-strength outdoor car body water-based paint according to claim 1 is characterized in that: Photoinitiators include: 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone, and the mass ratio of 2,4,6 (trimethylbenzoyl) diphenyl phosphine oxide and 1-hydroxy-cyclohexyl-phenyl ketone is 0.5-1.5:

1.

3. The high-strength outdoor car body water-based paint according to claim 1 is characterized in that: Excipients include: Wetting agent, defoaming agent, leveling agent, pH adjuster, thickener.

4. The high-strength outdoor car body water-based paint according to claim 3 is characterized in that: The mass ratio of the wetting agent, the defoaming agent, the leveling agent, the pH regulator and the thickener is 1-2:1-2:1-2:1-2:1-2.

5. The high-strength outdoor car body water-based paint according to claim 1 is characterized in that: Dendritic silica is prepared by the following steps: adding a dendritic polymer template to an ethanol aqueous solution and stirring for 10-30 minutes, adding an ammonia aqueous solution dropwise thereto while stirring, and continuing to stir for 5-15 minutes, adding ethyl orthosilicate dropwise thereto while stirring, stirring for 5-10 hours, standing for 10-15 hours, adding a silane coupling agent and stirring for 1-2 hours, centrifuging, washing, and vacuum drying.

6. The high-strength outdoor car body water-based paint according to claim 5, characterized in that: The mass fraction of the ammonia solution is 15-20%, and the mass ratio of the dendrimer template, the ammonia solution, the tetraethyl orthosilicate and the silane coupling agent is 1-3:5-10:5-12:0.1-1.

7. The high-strength outdoor car body water-based paint according to claim 5, characterized in that: The dendrimer template is amino-terminated polyamidoamine or hyperbranched polylysine.

8. The high-strength outdoor car body water-based paint according to claim 1 is characterized in that: The carboxyl modified polystyrene microspheres are prepared by the following steps: adding the polystyrene microspheres to an ethanol aqueous solution and stirring evenly, adding azobisisobutyronitrile, α-methylacrylic acid and styrene under nitrogen protection, stirring at 60-80° C. for 5-15 hours, filtering, washing, drying and crushing.

9. The high-strength outdoor car body water-based paint according to claim 8, characterized in that: The mass ratio of polystyrene microspheres, azobisisobutyronitrile, α-methyl acrylic acid and styrene is 1-5: 0.01-0.1: 0.1-0.2: 0.1-0.

5.

10. A method for preparing the high-strength outdoor vehicle body water-based paint according to any one of claims 1 to 9, characterized in that: The steps include: S1. Mix water-based aliphatic polyurethane acrylate resin and water-based UV-curable polyurethane dispersion, add dendritic silica and carboxyl-modified polystyrene microspheres, and continue stirring for 10-30 minutes to obtain a premix; S2. Add photoinitiator, polyethylene glycol diacrylate monomer, polydipentaerythritol hexaacrylate monomer, dipropylene glycol methyl ether, propylene glycol, and auxiliary materials into water and stir for 10-30 minutes. Add premix and continue stirring for 10-20 minutes, and filter.

Citation Information

Patent Citations

  • Preparation method for carboxylated polystyrene-silicon dioxide composite super-hydrophobic coating

    CN103709425A

  • Preparation of one-component water-based paint for automobile chassis and preparation method thereof

    CN108485425A

  • Preparation method of submicron carboxyl functionalized polystyrene microspheres

    CN114773515A

  • Outdoor super-weather-resistant water-based light-cured wood coating and preparation method thereof

    CN115160919A

  • Nanoscale silicon dioxide composite thermal insulation material and preparation process thereof

    CN116376386A